Exploiting non-self-governing territory status: Western Sahara and the new EU/Morocco Sustainable Fisheries Partnership Agreement. Issue 1 (June 2020) - Allen, Stephen
Abstract : The 2018 European Union (EU)/Morocco Sustainable Fisheries Partnership Agreement (SFPA) was negotiated in the aftermath of the Court of Justice of the European Union's (CJEU) 2018 Western Sahara Campaign judgment, which concerned a challenge to the 2006 EU/Morocco Fisheries Partnership Agreement (and its 2013 Protocol). This article first sets out the way in which the CJEU harnessed Western Sahara's status as a non-self-governing territory (NSGT) for the purpose of its finding that the EU/Morocco fisheries agreements were inapplicable to Western Sahara's coastal waters in the absence of third-party consent. However, the Court's approach left open the possibility that such agreements could be revised and extended to this marine area. Against this background, the article considers how the EU Commission and Council have responded to the CJEU's judgment in this case and, specifically, the way they have sought to justify the SFPA's de jure application to the waters off Western Sahara. In so doing, it shows the extent to which the SFPA's terms, and the circumstances surrounding its development, are deeply problematic as far as the exploitation of the territory's marine living resources is concerned. In this regard, it is hard to avoid the conclusion that the renewed EU/Morocco fisheries partnership undermines the EU's proclaimed commitment to the duty of non-recognition and the operation of the right to self-determination in this fraught context.